Building Capacity as Anchor Institutions: Infrastructure, Structure, and Strategy - Kristin Elise Norris; H. Anne Weiss (Coalition of Urban and Metropolitan Universities, 2019)
As campuses embrace their role as anchor institutions, considerations should be given to the role of infrastructure, structure, and strategy. This article differentiates between infrastructure and organizational structure then identifies implications for determining who should be involved based upon the institutional and community goals. Resources and infrastructure-a center or office that supports and coordinates community engagement-has been noted as a key component to the institutionalization of community engagement (Welch & Saltmarsh, 2013). How might the infrastructure used to support community engagement differ from the anchor institution mission? This article will illustrate potential differences and similarities while offering recommendations and considerations that would be useful as campuses develop their anchor institution plans.